Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1109/ultsym.2007.133
|View full text |Cite
|
Sign up to set email alerts
|

6E-5 High Performance and Miniature Surface Acoustic Wave Devices with Excellent Temperature Stability Using High Density Metal Electrodes

Abstract: Currently, miniature surface acoustic wave (SAW) devices (filters and duplexers) with a good temperature stability are strongly required. In order to realize its requirement, various SAW substrates combining a high density metal electrode and a substrate were researched. Combination of SAW substrates using high density metal electrodes offers excellent properties such as large electrode reflection coefficient, large mechanical coupling factor, low velocity, and good temperature stability. This paper reviews fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 19 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…This can be achieved by combining different layers of materials with different properties; this technique enables to reduce the temperature coefficient of frequency down to 5 ppm or less. [19][20][21][22] Nevertheless, SAW filters represent an important part of the market because they are easy to make; moreover, many companies in the world produce them.…”
Section: Surface Acoustic Wave Filtersmentioning
confidence: 99%
“…This can be achieved by combining different layers of materials with different properties; this technique enables to reduce the temperature coefficient of frequency down to 5 ppm or less. [19][20][21][22] Nevertheless, SAW filters represent an important part of the market because they are easy to make; moreover, many companies in the world produce them.…”
Section: Surface Acoustic Wave Filtersmentioning
confidence: 99%
“…On the other hand, the input energy from the transmitter group in two port SAW device will propagate across the delay line between the two transducers, and detected at the receiver electrodes. SAW devices are widely used in mobile phone technology [1], wireless communication [2], telecommunication [3] and recently, an extensive work focus on biosensor [4], microfluidic [5], microtransport [6] and actuation [7] applications. In this work, we developed a focusing SAW device adopting annular interdigital electrodes to generate high intensity acoustic fields.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a high phase velocity and large K 2 , designing low-loss and miniature SAW devices such as single phase unidirectional transducers (SPUDTs), RF filters and duplexers requires a large reflectivity in the interdigital transducers (IDTs) [8][9][10][11][12][13][14][15]. For example, Kadota et al suggested a reflection coefficient of 0.15 for designing wideband code division multiple access (WCDMA) duplexers [11].…”
Section: Introductionmentioning
confidence: 99%